A novel gold-polymer-antibody conjugate for targeted (radio-photothermal) treatment of HepG2 cells. Issue 1 (2nd January 2023) - Darwish, Wael M.; Bayoumi, Noha A.; El-Shershaby, Hanan M.; Moustafa, Kamel A.
Abstract: Localization of the near-infrared (NIR) plasmonic nanoparticles at the tumor sites is essential for safe and efficient photothermal therapy of cancer. In this work, two biocompatible polymers: modified poly(ethylene glycol) (PEG) and branched polyethyleneimine (bPEI) were used to bind plasmonic hollow gold nanospheres (HAuNS) to the tumor-specific antibody, atezolizumab (ATZ). The photo-immunoconjugate (HAuNS-PEI-PEG-ATZ) was prepared via a simple and cost-effective procedure. The conjugate was also prepared with the radioiodinated antibody (ATZ- 131 I) to combine the targeted radio- and photothermal cytotoxic actions against human hepatoma (HepG2) cells. In vitro study revealed that attachment to the antibody and the use of cellular internalizing polymers enhanced the cellular localization of both gold and the radiotherapeutic Iodine-131. Compared to bare gold nanoparticles, (HAuNS-PEI-PEG-ATZ) conjugate exhibited a significantly enhanced photothermal ablation of HepG2 cells after laser irradiation (0.4 W cm −2, 5 min). Laser irradiation of the cells treated with the radiolabeled conjugate (HAuNS-PEI-PEG-ATZ- 131 I) exhibited the highest cytotoxicity against HepG2 cells due to the combinatorial cytotoxic effects. Graphical Abstract: UF0001